Aktualisasi Distribusi Risiko dan Kelas Sosial Ulrich Beck: Studi Kasus Kabut Asap di Riau - Hanafi Saputra; Ahmad Hidayah* (Jurnal Karya Ilmiah Multidisiplin (JURKIM), 2023)
This study aims to analyze the contextualization of Beck's thoughts about the distribution of risk and social class in the case of the haze that hit the people of Riau. This study uses qualitative research methods with Ulrich Beck's theory of risk distribution as a tool to analyze research findings. This study shows that the effects of industrialization of palm oil and the haze are the risk from the haze in Riau is not only experienced by a group of people, but the risk is consumed by everyone. The existence of a class has no effect in terms of the spread of this risk consumption, it's just that there is a difference in consuming it. This can be seen from the ability of those from the upper middle social class to be better able to minimize risk exposure than those in the lower middle social class.